Digital Transformation and the Future of Public Libraries in China: Assessing Innovations, Challenges, and User Engagement - Yuan Liu; Jiajia Huang; Yuhan Wang (Studies in Social Science & Humanities, 2024)
This study explores the digital transformation of public libraries in China, focusing on innovations, challenges, and user engagement. It examines how libraries have implemented digital collections, developed online services, and adopted smart technologies to enhance accessibility and user experience. The research identifies key challenges such as funding constraints, technological disparities, and staff training needs. It also analyzes user engagement with digital services, highlighting areas for improvement based on survey results and community feedback. Additionally, the study evaluates the impact of digital transformation on library usage, noting shifts in physical and digital resource consumption. Finally, it outlines future directions and provides strategic recommendations and policy suggestions to support the continued evolution of public libraries in China.